“They accept me, because I was one of them”: formative qualitative research supporting the feasibility of peer-led outreach for people who use drugs in Dakar, Senegal - Stengel, Camille May; Mane, Famara; Guise, Andrew; Pouye, Magath; Sigrist, Monika; Rhodes, Tim (Harm reduction journal, 2018)
Background Peer outreach harm reduction initiatives are being developed with and for people who use drugs in Dakar, Senegal. This is in response to growing injecting drug use across the West Africa region and linked emerging epidemics of HIV and hepatitis C. We undertook formative qualitative research to explore the feasibility and potential of peer outreach in this context and in particular how outreach could be linked to fostering community-level processes of change. Methods We undertook a total of 44 semi-structured qualitative interviews. Thirty-four interviews were with people who used drugs (comprised of 25 participants who had injected at least once in their life) and included 11 peer educators who delivered “awareness-raising” harm reduction activities. We also interviewed 10 service providers involved in the planning and monitoring of peer outreach initiatives. We used thematic analysis to identify key characteristics of how peer-led outreach is being delivered, beneficiary need, and the nature of the social networks in which the awareness-raising activities operate. Results Through interviews with peer educators, people who use drugs, and service providers, four main overlapping themes are identified as follows: peer educators as a bridge to responsibilization through awareness-raising activities, awareness-raising activities as an enactment of recovery, awareness raising through social network diffusion, and the contexts and constraints of peer outreach engagement through awareness-raising activities. Conclusions The study results suggest that peer education is on a trajectory to develop into a central role for harm reduction interventions in Dakar, Senegal. This research shows how peer education is bound in processes of responsibilization and self-change, which link to varying possibilities for risk reduction or recovery. For peer education to achieve a range of significant goals, broader structural and system changes should be implemented in the region. We caution that without such changes, awareness-raising activities and the role of peer educators may instead become part of state- and agency-sponsored processes of seeking to responsibilize individuals for health and harm reduction.